Association Between Exclusive Breastfeeding and the Risk of Tonsilitis in Children Under Five in Demak, Central Java - Wardhana, Hendra; Kharisman, Ibnu; Stella, Paramita (Indonesian Journal of Medicine, 2018)
Background: Upper respiratory infection (URI) remains one of the primary causes of child mortality in Indonesia. Some studies have shown that exclusive breastfeeding can prevent various infectious diseases including URI. However, in some places the incidence of tonsilitis is still high although target of exclusive breastfeeding coverage has been met. This study aimed to determine association between exclusive breastfeeding and the risk of tonsillitis in children under five in Demak, Central Java.Subjects and Method: This was a cross sectional study conducted at 3 Community Health Centers, Demak, Central Java, from March to April 2017. A sample of 35 children under five years old were selected for this study. The dependent variable was the incidence of tonsillitis. The independent variable was history of exclusive breastfeeding. The data were collected by questionnaire. Tonsillitis was determined by history taking and physical examination. The data were analyzed by Fisher exact test.Results: Children without history of exclusive breastfeeding had an increased risk of contracting tonsillitis (OR= 9.58; p= 0.015) compared to those with history of exclusive breastfeeding.Conclusion: Provision of exclusive breastfeeding is associated with lower risk of tonsilitis in children under five.Keywords: tonsillitis, exclusive breastfeeding, children under fiveCorrespondence:Paramita Stella. Indonesian Doctor Internship Program, Bagas Waras Hospital, Klaten, Central Java.Indonesian Journal of Medicine (2018), 3(2): 71-76https://doi.org/10.26911/theijmed.2018.03.02.02